Exploiting the potential of next-generation sequencing in genomic medicine. (1st September 2016) - Pinto, Anna Maria; Ariani, Francesca; Bianciardi, Laura; Daga, Sergio; Renieri, Alessandra
ABSTRACT: Introduction : The review highlights the impact of next-generation sequencing (NGS) on genomic medicine and the consequences of the progression from a single-gene panel technology to a whole exome sequencing approach. Areas covered : We brought together literature-based evidences, personal unpublished data and clinical experience to provide a critical overview of the impact of NGS on our daily clinical practice. Expert commentary : NGS has changed the role of clinical geneticist and has broadened the view accomplishing a transition from a monogenic Mendelian perspective to an oligogenic approach to disorders. Thus, it is a compelling new expertise which combines clinical evaluation with big omics data interpretation and moves forward to phenotype re-evaluation in light of data analysis. We introduced the term, 'exotyping', to highlight this holistic approach. Further, the review discusses the impact that the combination of genetic reprogramming and transcriptome analysis will have on the discovery of evidence-based therapies.